Gender Differences in Financial Technology (FINTECH) Adoption in Indonesia: An Analysis of Risk Perceptions and Benefits - Juita, Verni; Pujani, Vera; Rahim, Rida; Rahayu, Rita (Universitas Muhammadiyah Surakarta, 2023)
This study aims to examine the gender differences in Fintech services adoption in Indonesia using the risk-benefit framework. This framework assumes that the user behaviours in adopting Fintech services are simultaneously affected by the positive factors (perceived benefits) and negative factors (perceived risks. The study utilized the snowball sampling data collection technique to gather data from 446 male and female online respondents. Smart PLS 3.0 was used to analyze the data and found that perceived benefits have a greater impact on the intention to adopt fintech services compared to perceived risks. Moreover, this study also reveals that, when examining gender-based differences in perceived benefit, both gender groups chose the convenience factor as the most dominant compared to the other two factors. In terms of risk perception, men tend to prioritize legal risk when using fintech services. This is because uncertainty in the legal aspect greatly affects their willingness to use these services. On the other hand, operational risk emerges as the dominant risk for women. This finding aligns with previous research, which emphasizes women's sharp attention to technical and operational issues in technology adoption.